Co-Morbidities as Predictors of Airflow Limitation among Smokers in England - Reem Kayyali; Yusur Hassan; Iman Hesso; Roshan Siva (MDPI AG, 2018)
The prevalence of co-morbidities among patients with Chronic Obstructive Pulmonary Disease (COPD) is well documented in the literature. Therefore, this pilot study aimed to identify whether co-morbidities screening would enhance COPD case-finding. Smoking patients were approached at Croydon University Hospital and two local community pharmacies (CPs). Their co-morbidities, respiratory symptoms, smoking pack-years and exercise capacity were collected. Airflow limitation was determined using handheld spirometry (COPD-6) device. The prevalence of airflow limitation was 42% (n = 21/50). The main identified predictors of airflow limitation were: co-morbidities (OR = 9, CI: 1.04–77.81, p = 0.025), respiratory symptoms (OR = 33.54, CI: 1.06–11.77, p = 0.039) and smoking history of ≥20 pack-years (OR = 3.94, CI: 1.13–13.64, p = 0.029). CPs were the main location for case-finding. This study demonstrated the need to screen for co-morbidities for COPD case-finding within CPs.